Apreensão linguística do evento infidelidade: identificação dos participantes em espanhol mexicano - Monsiváis, Raúl E. (2025)
This article aims to analyze through operational linguistics the techniques used by Mexican Spanish to encode the event/concept of INFIDELITY. This paper is part of a larger study that analyzes how different languages linguistically apprehend this event. However, Spanish provides interesting data on its own and, on this occasion, we will stop to analyze how the participants of the INFIDELITY event are linguistically apprehended. This ranges from the use of the term "infidel" as an adjective to its use as a noun, as well as other noun phrases by which the participants of said event are identified. For this study we use a heterogeneous corpus taken from magazine articles, literary texts and everyday life speech, among others. With this article we intend to contribute to studies in semantics, linguistic variation and other topics concerning linguistics in general.